Occupational Stress among Nurses of tertiary Care Hospitals in Tiruvarur - Sasikala, R.; Ramu, Dr.G. (International Journal of Scientific Research and Management (IJSRM), 2018)
Stress is physiological and psychological response towards any occurrences. It is very much vitalto learn about occupational stress because as it deters health and decreases the quality of work of nurses. The main objective was to determine prevalence, intensity and causes of occupational stress among nurses.Hospital based analytical cross-sectional study was conducted from January to November 2017 at two tertiary care teaching hospitals of Tiruvarur. The study was carried out on 265 registered nurses, having valid license by Tamil Nadu Nursing Council. Convenient non-probability method was used to access subjects. After taking consent, semi-structured and pre-tested occupational stress questionnaire was used to obtain the data. The study results revealed that majority of nurses 125 (47.2%) were between 25 to 30 years of age.Maximum ratio of nurses were female 160(60.4%) and out of them 148(55.8%) were married. Two hundredand one (75.8%) were diploma holders in nursing, while only 2(0.8%) had done their master in nursing. Thestudy participants reported to suffer with job related stress; mild stress 2.0%, moderate stress 36.5% and severe61.5%.